Drenagem em obras de engenharia - estudo de caso: cidade de José da Penha - RN - Queiroz Filho, Leogilton Fontes de (Universidade Federal Rural do Semi-Árido, 2019)
Urban planning for water resources in large, medium and small cities is largely ineffective. The surface drainage is done by curb, the cans and the mouths of wolf are not so unique as the municipal managements. For the city of José da Penha, besides the superficial drainage, there is a problem with the brake and its outcrop. This work has the objective of presenting a proposal of evaluation for a level of flood, making feasible an implantation of equipment of coexistence and leisure for the community. The methodology used was the documentary research, followed by the occupational analysis, the topographic survey and the comparative data among those that received the highest index of water accumulation in the study region. Losing only 27 days, with an accumulation of 130.9mm, was enough to render the land unusable during its flooding. From a perspective, the resources of methods for lowering the water table by the use of vertical drainage and a layer of drainage material, with the aim of redirecting the water to a suitable place, similarly weaken the carrying out of further studies and the realization of tests to search for more accurate data, such as a soil survey.
Monografia
Keywords: Planejamento urbano; drenagem; lençol freático; Urban planning; drainage; water table; ENGENHARIAS::ENGENHARIA CIVIL